A VNA-Based Wideband Measurement System for Large-Signal Characterization of Multiport Circuits - Schulze, Christoph; Mengozzi, Mattia; Gibiino, Gian Piero; Angelotti, Alberto Maria; Florian, Corrado; Santarelli, Alberto; Heinrich, Wolfgang; Bengtsson, Olof (IEEE transactions on microwave theory and techniques, 2024)
This work reports on a wideband (WB) measurement system based on a vector network analyzer (VNA) topology for multiport large-signal measurements. The setup exploits a modified commercial VNA with WB intermediate frequency (IF) outputs that allow for more than 5-GHz analysis bandwidth (BW), where the IF is captured using an external high-speed oscilloscope. A three-port configuration using six receivers is described, together with the signal processing to achieve the high dynamic range required for WB signal measurements. The calibration procedure to establish reference planes at the three ports of the device-under-test (DUT) is shown. A comparison is made between single-tone continuous-wave (CW) calibration and WB calibration using multitone signals, illustrating advantages, challenges, and limitations. The system is then demonstrated for on-wafer WB characterization and linearization of a dual input Doherty power amplifier (DIDPA) using a 100-MHz instantaneous BW excitation signal at millimeter-wave frequencies. By leveraging on the error-corrected WB waves, an algorithm is proposed for modulated input signal control across a 600-MHz acquisition BW at the DUT on-wafer reference planes. The algorithm enables a user-defined emulated splitting of the input WB signals. The linearization performance of such an emulated PA configuration is finally evaluated.